Principles and practices of management - Bhivpathaki, Deepak P...[et al] (Everest Publishing House, 2011)
Principles and practices of management / Bhivpathaki, Deepak P...[et al]. -- Pune: Everest Publishing House, 2011 658.4 P954e12 12th ed No. of Copies : 1